Do hubristic managers really matter on performance? Evidence from listed firms in Nigeria - Ayobolawole Adewale Ogundipe; Abiodun Rafiat Ayeni-Agbaje; Opeyemi Roselyn Akindutire (The Indonesian Journal of Accounting Research, 2020)
This study examined whether or not hubristic managers affect the performance of listed firms in Nigeria for the period of 2007-2017. Based on Fixed panel estimator, our study reveals that determinants of hubristic managers such as age, tenure, ownership and political appointment are adversely affecting the performance of listed firms in the country, while business climate, size of the firm and earnings deviation are mixed indicators of listed firms’ performance in Nigeria. We propose that the regulating agencies of government in charge of listed firms should reduce the age bracket of CEOs in the country, percentage of shares owned by CEOs in the country should be reduced. Also, firms should not be allowed to make people with political connections or those who are once or presently in a political office a CEO because of its adverse effect on the performance of listed firm in the country.